Ultrasound screening for fetal anomalies in a single center: diagnostic performances twenty years after the Eurofetus Study. (12th December 2022) - Sileo, Filomena G.; Finarelli, Alessandra; Contu, Giannina; Lugli, Licia; Dipace, Vincenza; Ballarini, Michela; Guidi, Cristina; Facchinetti, Fabio; Bertucci, Emma
Abstract: Purpose: To establish the accuracy of ultrasound in detecting fetal anomalies looking at the concordance between prenatal and postnatal diagnosis. Materials and methods: Retrospective analysis of concordance between prenatal and postnatal/autoptic diagnosis of fetuses with congenital abnormalities. Data are from a single center (Policlinico di Modena); all fetuses included were born between 2017 and 2018 and with a follow-up of at least 6 months. We included all deliveries (including perinatal deaths) and termination of pregnancy (TOP) for fetal indication. We calculated sensibility, sensitivity, Positive and Negative Likelihood Ratio, positive and negative predictive value of ultrasound. Results: During the study period 5920 deliveries, including perinatal deaths, and 28 TOP for fetal indication were registered at our center. The prevalence of congenital malformations was 2.6% (153/5920). At least one ultrasound was performed in our center in 1250 women delivering in our unit. All 28 TOP had the anomaly scan performed in our center. Among the total 1278 women scanned in our unit, there were 128 (10%) suspicious scans. In 5/128 (3.9%) cases we diagnosed a false alarm; in 8/128 (6.2%) cases an evolutive malformation with in-utero regression. The prenatal diagnosis was confirmed in 77 (60.2%) cases at birth and in 28/128 (21.9%) at postmortem analysis while there were 10/128 false positive (7.8%). Among the 153 congenital malformations diagnosed at birth, the anomaly scan was performed in our Prenatal Medicine Unit in 92 (60.1%) fetuses. Among these, there were 15 false negatives (9.8%) while in 77/92 (83.7%) the malformation at birth agreed with the sonographic diagnosis. Sensitivity and specificity of ultrasound were 87.5% (IC95 80.2–92.8%) and 99.1% (IC95 98.4–99.6%) respectively with a Positive Likelihood Ratio and Negative Likelihood Ratio of 101.3 (IC95 54.5–188.5) and 0.13 (IC95 0.08–0.2); Positive Predictive Value and Negative Predictive Value were 91.3% (IC95 85–95.1%) and 98.7(IC95 98–99.2%). Conclusion: Anomaly scan in pregnancy allows the diagnosis of congenital malformations with a sensibility of 87.5% and specificity of 99.1%. The main limitations of this study are its retrospective design and that it was conducted in a single referral center.